A call to action to inform patient‐centred approaches to obesity management: Development of a disease‐illness model. Issue 3 (11th April 2019) - Fastenau, John; Kolotkin, Ronette L.; Fujioka, Ken; Alba, Maria; Canovatchel, William; Traina, Shana
Abstract : Patient‐centred care is an essential component of high‐quality health care, shown to improve clinical outcomes and patient satisfaction, and reduce costs. While there are several authoritative models of obesity pathophysiology and treatment algorithms, a truly patient‐centred model is lacking. We describe the development of a patient‐centric obesity model. A disease‐illness framework was selected because it emphasizes each patient's unique experience while capturing biomedical aspects of the disease. Model input was obtained from an accumulation of research including contributions from experts in obesity and patient‐reported outcomes, qualitative research with adults living in the United States, and two targeted literature searches. The model places the patient with obesity at its core and links pathologic imbalances of energy intake and expenditure to environmental, sociodemographic, psychological, behavioural, physiological and medical health determinants. It highlights relationships between obesity signs and symptoms, comorbid conditions, impacts on health‐related quality of life, and some barriers to obesity management that must be considered to attain better outcomes. Providers need to evaluate patients holistically, understand what changes each patient is motivated to make, and recognize what challenges might impede weight reduction, improvements in comorbid conditions, signs and symptoms, and health‐related quality of life before pursuing individualized treatment goals. Patients living with obesity who do lose weight perceive benefits beyond weight loss. Ideally, this model will increase awareness of the complex, heterogeneous impacts of obesity on patients' well‐being and recognition of obesity as a chronic disease, and prompt a call to action among stakeholders to improve quality of care.